Career Guidance and Counseling at The Work, Community, Employees and Retirements - Jecsy Anadiora; Afdal Afdal; A Muri Yusuf (SCHOULID: Indonesian Journal of School Counseling, 2021)
Career guidance is needed both starting from the education period at school and up to the world of work. For this reason, being able to determine the right career choice for adults requires a long process, namely career planning which is influenced by the level of development. Guidance and counseling in the world of work helps workers to help solve problems and develop themselves. Counseling for retirement is held solely to prepare older employees for retirement. Career guidance should indeed be carried out at an early age to develop one's potential. The problems encountered in the field are the unpreparedness of the community to develop their potential and the lack of services from the government, therefore  take advantage  career counseling in  workplace, community, employees and retirees.